THE IMPORTANCE OF PROVIDING MOTIVATION TO BRING WORK SPIRIT THAT IMPACT ON INCREASING PERFORMANCE - Noviani, Elena (Perhimpunan Sarjana Ekonomi dan Bisnis, 2021)
Performance is tangible evidence of good institutional governance. However, performance will not be achieved if the employees do not have a good work spirit. Therefore, the leadership and management need to pay attention to the factors that cause the increase or decrease in morale that has an impact on performance. This study aims to analyze the motivational factors that affect performance, either partially or simultaneously. The research method uses quantitative questionnaires as a data collection tool. While the data analysis was done by using linear regression statistical technique. The object of research is the religious court in Tangerang district. The results of the study show that employees are required to provide good work results in the right ways (regulated by procedures, policies, and work discipline). However, the employees realized that enthusiasm was needed in realizing these demands. That is, in carrying out the task required a driver who strengthens the heart and strengthens positive feelings, so that a feeling of pleasure and enthusiasm is born in work